Implementation of Project-Based Learning (PjBL) Model in Nurturing Literacy Skill at Namira School Probolinggo Elementary School - arya wardana, ludfi; Mochamad Nursalim; Diana Rahmasari (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
Literacy is a key skill for the future, as good literacy enables one to understand, analyze, and use information effectively. At the moment, literacy is of little interest to students. It causes a lack of student ability in literacy. Literacy is boring for students. Even though literacy is necessary for daily life and useful in various fields, the disinterest of students makes Indonesia's literacy scores the worst in the world. This study aims to describe the implementation of the project-based learning (PjBL) learning model on students' literacy skills at Namira School, Probolinggo Elementary School. Methodology A qualitative approach with a naturalistic inquiry type of research is the approach used in this study. Data collection in this investigation used several techniques, namely interviews, observation, and documentation. Based on the results of the study, it can be concluded that teachers have succeeded in improving literacy skills in 4th grade students at Namira School Probolinggo Elementary School, especially in science literacy. This is evident from the presentation results for each group. All groups are able to explain the changes in the form of substances that occur, namely the change in the form of liquid to solid substances that occur in pudding.